2019
DOI: 10.1111/1759-7714.12956
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of preoperative platelet, fibrinogen, and D‐dimer levels in patients with non‐small cell lung cancer: A multicenter prospective study

Abstract: BackgroundThe relationships between coagulation factors and non‐small cell lung cancer (NSCLC) prognosis have been intensively studied. However, no previous study has investigated the combined effects of preoperative platelet (PLT), fibrinogen (FIB), and D‐dimer (D‐D) levels on the prognosis of NSCLC.MethodsA multicenter prospective study was conducted over seven hospitals. A total of 395 patients diagnosed with operable NSCLC for the first time were included and followed‐up until disease progression or the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 33 publications
0
43
1
Order By: Relevance
“…24 D-dimer levels were higher than baseline in patients who developed VTE after surgery, and studies have shown that preoperative levels of D-dimer had an impact on survival of NSCLC patients. 16 However, it seems irresponsible to omit the fluctuations of D-dimer levels after surgery. Actually, increased attention is being paid to long-term D-dimer level changes and the relationship with VTE, 36 and in our experience, a more meticulous tracking of D-dimer levels can depict a more detailed hematological profile, and can be achieved by following the level changes closely in adjacent days instead of at subsequent relatively longer intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 D-dimer levels were higher than baseline in patients who developed VTE after surgery, and studies have shown that preoperative levels of D-dimer had an impact on survival of NSCLC patients. 16 However, it seems irresponsible to omit the fluctuations of D-dimer levels after surgery. Actually, increased attention is being paid to long-term D-dimer level changes and the relationship with VTE, 36 and in our experience, a more meticulous tracking of D-dimer levels can depict a more detailed hematological profile, and can be achieved by following the level changes closely in adjacent days instead of at subsequent relatively longer intervals.…”
Section: Discussionmentioning
confidence: 99%
“…13 D-dimer, as an end production of fibrin degradation, is a strong indicator of VTE, which also predicts prognosis and long-term survival after antitumor therapy. [14][15][16][17] Many prediction models that integrated D-dimer as a necessary index have been developed to predict the incidence of cancer-associated VTE and to stratify patients by different degrees of risk. [18][19][20][21][22] However, almost every model used preoperative D-dimer test results as a stationary index, and may therefore have missed the dynamic trend of D-dimer concentration after surgery which then causes bias when these models are employed.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma D-dimer is the product of cross-linked fibrin degradation by plasmin-induced fibrinolytic activity, and this marker has been widely used as a useful indicator of hemostasis and fibrinolysis activation. Elevated preoperative plasma D-dimer levels have been reported to be an unfavorable prognostic factor in various malignancies, such as lung cancers, 6,15 digestive tract cancers, 16 urological cancers 10,11,17 and soft tissue sarcomas. 5,7 The mechanism underlying the association between elevated plasma D-dimer levels and malignancy remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Preoperative factors, namely body mass index, advanced age, delayed surgery, hydronephrosis, tumor location, and neutrophil-lymphocyte ratio (NLR) are associated with poor prognosis. 3 Several studies have demonstrated an association between malignancy and hemostasis biomarkers 5,6 with tumors associated with high levels of coagulation markers (fibrinogen) and thrombogenesis markers (D-dimer). D-dimer is a cleavage product of fibrin, which is produced by plasmin-induced fibrinolysis, 7 and this biomarker indicates the activation of hemostasis and fibrinolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation